Analisis Keuntungan dan Kerugian Pemanfaatan Iradasi Sinar Gamma di Bidang Pertanian Padi - Cindy Ineke Ferdanti; Lisa Listyo Wati; Regena Yuni Maulida; Rifati Dina Handayani; Sri Astutik (Jurnal Ilmiah Wahana Pendidikan, 2023)
Rice plants are rice-producing plants which are very important commodities for the State of Indonesia. Aside from being a staple food producer, rice is also the main source of income for millions of farmers in the country. To improve the quality of rice and increase its economic value, breeding is carried out to correct weaknesses and overcome some of the problems that occur. One of the rice plant breeding methods that can be used is by using gamma ray irradiation technique. This study aims to analyze the advantages and disadvantages of using gamma rays in rice farming. This research uses the Article Review method with a total of 30 articles published in 2010-2022. The data obtained were then analyzed using descriptive analysis techniques. From the results of the study, it was found that gamma rays proved to provide several advantages, namely increasing plant height, increasing the number of tillers, increasing panicle length, shortening harvest time (during early maturity), shortening flowering time, resistance to wareng pests, and changing some properties such as the shape of grain tips that do not hairy. Meanwhile, using gamma rays as a physical mutagen technique, in some types of local rice varieties, if the dose used is too high, it will result in several disadvantages, namely reduced growth in callus diameter, callus growth capacity, seedling height or plant height, leaf width, flowering age, harvest age, as well as the number of children.